Digital Government: Business Model Development For Public Value Creation - A Dynamic Capabilities Based Framework - Wirtz, Bernd W.; Langer, Paul F.; Schmidt, Florian W. (Public administration quarterly, 2021)
Rapid advances and the spread of digital technologies have changed the expectations of citizens, firms and organizations towards government services, which increasingly receive the call to transform services and structures according to changed needs and preferences. The concept of business model development provides a suitable approach for public institutions aiming at adjusting their services and operations. Since government institutions increasingly develop new services and products, this study provides a theoretic foundation to operational readiness as well as a guideline how to set up digital business models in a public sector context. Therefore, a framework is derived from conceptual studies in the field as well as related theoretical concepts such as business model theory in the public sector context, dynamic capacities and public value creation. Building on this foundation this study conceptualizes a process of business model development to create user oriented digital services in the public sector.